Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas Dan Risiko - Sri Setia Ningsih (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2017)
The purpose of this research is to know about working capital management applied, and its influence on profitability and risk. The research object is trading company moves in import & distribute chemical raw material. The research used analysis descriptive method, and the hypothesis was testing by simple linier regression, correlation, and determination. The result of the research shows that the effect of the implementation of working capital management on the change of the net working capital with tend to rise has a profitability level of 10.4% lower than the net working capital change with tend to go down of 46%, but instead on the risk level, the net working capital change with tend to rise has a risk level of 43.8% higher than the change in net working capital with tend to go down of 0.3%.Based on t test, the result shows that the net working capital change influence is not significant to profitability and risk.